Impact of spider nevus and subcutaneous collateral vessel of chest/abdominal wall on outcomes of liver cirrhosis - Hongyu Li (Termedia Publishing House, 2019)
Introduction Spider nevus and subcutaneous collateral vessel of the chest/abdominal wall are common in liver cirrhosis. This prospective study aimed to evaluate the impact of spider nevus and subcutaneous collateral vessel of the chest/abdominal wall on the outcomes of cirrhotic patients.